The output-inflation trade-off in Canada - Stefano Gnocchi; Fanny McKellips; Rodrigo Sekkel; Laure Simon; Yinxi Xie; Yang Zhang (Bank of Canada, 2024)
We explain how the Bank of Canada's policy models capture the trade-off between output and inflation in Canada. We start by briefly revisiting the determinants of the New Keynesian Phillips curve. Next, we provide an overview of the Phillips curves that are currently embedded in the two main policy models the Bank uses for macroeconomic projections and analysis, known for short as ToTEM and LENS. We then discuss the challenges in identifying the trade-off between output and inflation and provide new estimates of the trade-off using recently proposed methods. Finally, we contrast these estimates with the ones in the Bank's policy models.
Keywords: E31; E52; 330; Business fluctuations and cycles; Econometric and statistical methods; Inflation and prices; Monetary policy transmission